(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2025)
This article analyzes the film Roma (Alfonso Cuarón, 2018) as a pivotal artifact of cultural memory within Netflix’s global expansion strategy. It argues that the platform, moving beyond its commercial model, positions itself as a manager of historical imagination, thereby transforming local memory into a negotiable transnational asset. The study is structured around two complementary dimensions: the intermedial, which examines the asymmetric production conditions between transnational capital (Netflix/Participant Media, with their distinct political and commercial agendas) and local capital (Esperanto Filmoj, managing authenticity on the ground); and the intramedial, which dissects the film’s rhetoric conceived as an archive. This second dimension explores how sensitive spaces, objects, and sounds are documented and ordered to construct an immersive and affective memory, primarily through the use of long takes and panning shots that foster a sensory experience of the past. The central paradox lies in the fact that Roma, while evoking an intimate and seemingly authentic memory, is the product of a complex power mediation that globalizes, standardizes, and commercializes history. The article concludes that Netflix, through paradigmatic films like this, acts as an agent that homogenizes and globally distributes “glocal” memories. This raises a fundamental question: can an archive controlled by a corporation, whose ultimate logic is commercial, preserve and promote critical narratives of the past? Or does its mediation inevitably turn historical memory into just another cultural product, subject to the dynamics of the market and global consumption?